Transcutaneous nerve stimulation for pain relief during chest tube removal following cardiac surgery - Vishwas Malik; Usha Kiran; Sandeep Chauhan; Neeti Makhija (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: In patients undergoing open heart surgery, chest tubes are removed postoperatively when patients are well awake and stable. Pain during chest tube removal can be moderate to severe and can be the worst experience of hospitalization. Various modalities of pain relief during chest tube removal have been tried with variable results. We sought to examine the effect of transcutaneous electrical nerve stimulation (TENS) as an intervention for pain relief during chest tube removal after cardiac surgery. Material and Methods: In a tertiary care center, fifty patients undergoing open heart surgery were randomized into two groups. Group TENS (n = 25) received TENS from 30 min before and continued up to 30 min after chest tube removal. Control Group (n = 25) did not receive TENS. In both the groups, additional analgesic medication was provided on demand, besides the standard analgesic regime which was injection ketorolac 30 mg intramuscularly every 8 h. Patients were studied for pain during chest drain removal and pain related nausea, vomiting, and sense of well-being. Results: Mean visual analog pain score assessed for chest tube removal was significantly less 4.1 ± 1.2 (P < 0.05) in TENS Group as compared to 6.1 ± 0.8 in Control Group. Significantly greater number of patients (n = 14) (P < 0.05) in Control Group demanded additional analgesia as compared to TENS Group (n = 5). Feeling of well-being, improvement in appetite, and sleep was better in TENS Group as compared to Control Group. Conclusion: We conclude that TENS might not replace the conventional analgesics but has definite adjuvant role in decreasing pain scores and improves sense of well-being during chest tube removal after cardiac surgery.